Heavy metals contamination and potential health risk in highland river watershed (Malaysia) - Razali, Azlini; Syed Ismail, Sharifah Norkhadijah; Awang, Suriyani; Praveena, Sarva Mangala; Zainal Abidin, Emilia (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2018)
Introduction: Extensive agriculture activities in the upstream area causes pollutants flow to the downstream area and contaminate the drinking water resources. Methods: Water samples were collected from 27 sampling points of Bertam River in Cameron Highlands, during wet season in September 2017 for physicochemical properties and heavy metals analyses. Potential health risk was calculated based on the heavy metals concentration detected. Results: The pH value of the river ranged from neutral to slightly acidic (6.15-7.01). The overall mean level of turbidity (109.94 ± 160.73 NTU), DO (7.86 ± 0.71 mg/L), E. coli (5191.00 ± 14937.42 CFU/100 mL), and NH3-N (0.85 ± 0.54 mg/L) were exceeded the National Standard for Drinking Water Quality (NSDWQ) (Ministry of Health Malaysia). The concentration of heavy metals were in the following order; Fe>Al>Cu>Zn>Pb>Cd. The overall mean concentration of Cd (0.015 ± 0.007 mg/L), Fe (0.442 ± 0.191 mg/L) and Pb (0.021 ± 0.005 mg/L) were exceeded the national standard (NSDWQ). The non-carcinogenic health risk for adult and children from daily water consumption was within an acceptable risk. There is a potential cancer risk through Cd exposure in the drinking water where the risk higher among children (4.92 x 10-3), followed by adult male (3.06 x 10-3) and adult female (2.98 x 10-3). Conclusion: Significant heavy metals contamination and health risk through water consumption were observed in the highland river watershed, possibly due to the anthropogenic activities.